ASSESSING CARRYING CAPACITY OF PABBI HILLS KHARIAN RANG E - J. Afzal; M. Arshad Ullah; M. Anwar (Journal of Animal and Plant Sciences, 2007)
A survey was conducted to assess the carrying capacity of the Pabbi Hills Kharian Range during the month of May, 2005. A total of 374.27 kg ha-1 dry matter was assessed using standard techniques. The livestock being raised in these areas were cattle and goats only. Average weight of a cow and a goat was estimated to be 300 and 25 kg, respectively. The annual requirement of dry matter per animal unit was estimated to be 2190 kg, which can be met through grazing of 12 ha / AU/ year carrying capacity.
Keywords: Animal unit; Carrying capacity; Forage; Mesquite